Answer:
<h2>x = -347 1/2</h2>
Step-by-step explanation:
When solving algebra, it is important the we follow the steps in correct order and check our answer at the end.
Step 1: Simplify by combining like terms
y = -x/2 + 5/4 + 8y = -25
Step 2: Substitute
y = -25
-25 = -x/2 + 5/4 + 8(-25)
-25 = -x/2 + 5/4 + -200
-25 = -x/2 - 198 3/4
Step 3: Answer
x = -347 1/2
Step 4: Check
y = 3/2x + 5/4 −2x + 8y = −25
-25 = 3/2(-347 1/2) + 5/4 −2(-347 1/2) + 8(-25)
-25 = -25✔️
Step 5: Verified Answer
x = -347 1/2
I'm always happy to help :)
Answer: (60.858, 69.142)
Step-by-step explanation:
The formula to find the confidence interval for mean :
, where
is the sample mean ,
is the population standard deviation , n is the sample size and
is the two-tailed test value for z.
Let x represents the time taken to mail products for all orders received at the office of this company.
As per given , we have
Confidence level : 95%
n= 62
sample mean :
hours
Population standard deviation :
hours
z-value for 93% confidence interval:
[using z-value table]
Now, 93% confidence the mean time taken to mail products for all orders received at the office of this company :-
![65\pm (1.8119)\dfrac{18}{\sqrt{62}}\\\\ 65\pm4.142\\\\=(65-4.142,\ 65+4.142)\\\\= (60.858,\ 69.142)](https://tex.z-dn.net/?f=65%5Cpm%20%281.8119%29%5Cdfrac%7B18%7D%7B%5Csqrt%7B62%7D%7D%5C%5C%5C%5C%2065%5Cpm4.142%5C%5C%5C%5C%3D%2865-4.142%2C%5C%2065%2B4.142%29%5C%5C%5C%5C%3D%20%2860.858%2C%5C%2069.142%29%20)
Thus , 93% confidence the mean time taken to mail products for all orders received at the office of this company : (60.858, 69.142)
Answer:
12 feet
Step-by-step explanation:
The answer is 56 cookies because i did math in my head
Answer:
![y-6 = -\frac{1}{2} (x+1)](https://tex.z-dn.net/?f=%20y-6%20%3D%20-%5Cfrac%7B1%7D%7B2%7D%20%28x%2B1%29)
Step-by-step explanation:
For this case we have two points given (-1,6) and (1,5)
And we want to complete the point slope equation of the line:
![y-6 = m(x-x_o)](https://tex.z-dn.net/?f=%20y-6%20%3D%20m%28x-x_o%29%20)
We need to find the slope and we can use the following formula:
![m = \frac{y_2 -y_1}{x_2 -x_1}](https://tex.z-dn.net/?f=%20m%20%3D%20%5Cfrac%7By_2%20-y_1%7D%7Bx_2%20-x_1%7D)
And replacing the info we got:
![m= \frac{5-6}{1-(-1)}=-\frac{1}{2}](https://tex.z-dn.net/?f=%20m%3D%20%5Cfrac%7B5-6%7D%7B1-%28-1%29%7D%3D-%5Cfrac%7B1%7D%7B2%7D)
And then the equation would be given by:
![y-6 = -\frac{1}{2} (x- (-1))](https://tex.z-dn.net/?f=%20y-6%20%3D%20-%5Cfrac%7B1%7D%7B2%7D%20%28x-%20%28-1%29%29)
And our final answer would be:
![y-6 = -\frac{1}{2} (x+1)](https://tex.z-dn.net/?f=%20y-6%20%3D%20-%5Cfrac%7B1%7D%7B2%7D%20%28x%2B1%29)